Localization of abelian gauge fields with Stueckelberg-like geometrical coupling on f(T, B)-thick brane - F. M. Belchior; A. R. P. Moreira; R. V. Maluf; C. A. S. Almeida (European Physical Journal C: Particles and Fields, 2023)
Abstract In the context of f(T, B) modified teleparallel gravity, we investigate the influence of torsion scalar T and boundary term B on the confinement of both the gauge vector and Kalb–Ramond fields. Both fields require a suitable coupling in five-dimensional braneworld scenarios to yield a normalizable zero mode. We propose a Stueckelberg-like geometrical coupling that non-minimally couples the fields to the torsion scalar and boundary term. To set up our braneworld models, we use the first-order formalism in which two kinds of superpotential are taken: sine-Gordon and $$φ ^{4}$$ ϕ 4 -deformed. The geometrical coupling is used to produce a localized zero mode. Moreover, we analyze the massive spectrum for both fields and obtain possible resonant massive modes. Furthermore, we do not find tachyonic modes leading to a consistent thick brane.